2023
DOI: 10.1021/acs.analchem.2c03946
|View full text |Cite
|
Sign up to set email alerts
|

In-Vitro Diagnostic Reagent Evaluation of Commercially Available Cardiac Troponin I Assay Kits Using H/D Exchange Mass Spectrometry for Antibody-Epitope Mapping

Abstract: Cardiac troponin I (cTnI) is the biomarker of choice and considered a gold standard for the diagnosis of acute myocardial infarction. However, the quantitative results of cTnI assay kits from different manufacturers are not comparable. Based on the H/D exchange mass spectrometry (HDX-MS) workflow, we developed an in-vitro diagnostic reagent antibody evaluation strategy to analyze the interactions of epitopes and antibody cocktails(R195, F12, S13) and (D1, D2, pAb2). The HDX results indicate that the quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Subsequently, others described polyclonal antibodies for study of immune response against tumor necrosis factor α (TNF-α) (Abbott et al, 2013) and factor H-binding protein (fHbp) (Ständer et al, 2021). Further, other investigators compared the immune response for a given antigen in different serum samples (Yang et al, 2016) to evaluate different diagnostic polyclonal antibodies against C-reactive protein, an important biomarker for inflammation (Sun et al, 2022) and recently against Cardiac troponin I (cTnI), a biomarker for acute myocardial infarction (Song et al, 2023). Such studies showcase the exquisite tolerance of HDX-MS for handling molecular heterogeneity, which is difficult with other structural methods.…”
Section: Using Automation and New Hardwarementioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, others described polyclonal antibodies for study of immune response against tumor necrosis factor α (TNF-α) (Abbott et al, 2013) and factor H-binding protein (fHbp) (Ständer et al, 2021). Further, other investigators compared the immune response for a given antigen in different serum samples (Yang et al, 2016) to evaluate different diagnostic polyclonal antibodies against C-reactive protein, an important biomarker for inflammation (Sun et al, 2022) and recently against Cardiac troponin I (cTnI), a biomarker for acute myocardial infarction (Song et al, 2023). Such studies showcase the exquisite tolerance of HDX-MS for handling molecular heterogeneity, which is difficult with other structural methods.…”
Section: Using Automation and New Hardwarementioning
confidence: 99%
“…Further, monoclonal antibodies are one of the fastest growing drug classes (Ecker et al, 2015;Martin, 2016;Reichert, 2023) (Figure 1) (as of this writing, 104 approved monoclonal antibodies are IgG, three Fabs, two ScFvs, one nanobody, and one DsFv (https://www.antibodysociety.org/resources/approvedantibodies/). Additionally, antibodies are widely used as analytical reagents for diagnostic tests and in research and development (Leinikki et al, 1993;Sun et al, 2022;Song et al, 2023). The introduction of monoclonal antibodies for therapeutic use was a paradigm shift in the pharma industry.…”
Section: Introductionmentioning
confidence: 99%
“…A wide array of detection methods support IVDs, including enzyme-linked immunosorbent assay (ELISA), immunofluorescence analysis (IFA), , radioimmunoassay (RIA), immuno-PCR, , photoelectrochemical (PEC), , nucleic acid hybridization, high-performance liquid chromatography (HPLC), mass spectrometry, electrochemiluminescence, fluorescence immunoassay, electrochemical immunoassay , and so on. Recent research efforts have increasingly focused on the development of advanced IVD devices.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Cardiac troponin I(cTnI) is a specific structural protein found in cardiac tissue that inhibits the binding of myosin to actin, and plays a crucial role in the process of cardiac contraction. 3,4 Numerous studies have demonstrated that cTnI exhibits significant changes in its concentration levels during the onset of acute myocardial infarction (AMI). 5 Additionally, cTnI offers advantages such as clear diagnostic thresholds, a wide window of detection, and rapid testing, making it a core biomarker for AMI diagnosis.…”
Section: Introductionmentioning
confidence: 99%